Comparison of Natural Hedges from Diversification and Derivative Instruments Agains Commodity Price Risk: A Case Study of PT Aneka Tambang, Tbk - Dwiparandi, Dikdik; Murtaqi, Isrochmani (The Indonesian Journal of Business Administration, 2013)
Antam is a mining company which most revenues come from the sales of diversified commodities, namely ferronickel (36.5% of total revenues in 2011), nickel ore (24.1%), gold (36.0%), silver (2.7%), and coal (0.8%). With the trend of declining nickel price in 2012, more than half of the companyÃ¢â‚¬â„¢s revenue is exposed to the nickel commodity price downside risk. Despite that, Antam claimed that its diversified commodities can reduce such impact, in other words it creates natural hedges, a hedging method that comes from daily activities. The topic of this final project is concerning the commodity price risk of nickel against AntamÃ¢â‚¬â„¢s natural hedge and other hedging tools. This research aims to find the strength of natural hedge compared with the use of derivatives to mitigate the risk of declining nickel price. Due to the limitation of data, only forward and option contract are used as derivative instruments. Risk in natural hedge is conducted by calculating the VaR of portfolio using Delta-Normal method, which then is compared to the companyÃ¢â‚¬â„¢s retained earnings in 2011. Forward and Option contracts are applied to ferronickel and nickel ore, which make four combinations of derivatives strategy. Comparison of natural hedge and derivatives is done by comparing VaR of natural hedge with the cost of hedging of derivatives strategy in three time horizon. Based on calculation, although AntamÃ¢â‚¬â„¢s natural hedges is strong, the company should hedge its nickel-based commodities in short period by entering ferronickel into put option contract and nickel ore into short forward contract. Antam may also improve its diversification by adjusting its sales volume per commodity or use both derivative instruments to each commodity. Ã‚Â Keywords: Commodity Price Risk, Value at Risk, Natural Hedge, Forward Contract, Option Contract.